Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
1. rule for 3: (x, y) ⇒ (x +4.5, y -1); rule for 4: (x, y) ⇒ (x -4, y +1)
2. 3: (-5.5, -2); 4: (4, -1.5)
Step-by-step explanation:
1.
The amount of translation that occurred from the initial position to the final position can be found by subtracting the initial from the final position.
player 3: (-1.5, 0) -(-6, 1) = (-1.5 +6, 0 -1) = (4.5, -1) . . . step 1 translation
This translation is added to (x, y) in the transformation rule:
(x, y) ⇒ (x +4.5, y -1) . . . . player 3 rule for step 1
__
Similarly, the rule for player 4 is found to be ...
player 4: (1, 0.5) -(5, -0.5) = (1 -5, 0.5 +0.5) = (-4, 1) . . . step 1 translation
(x, y) ⇒ (x -4, y +1) . . . . player 4 rule for step 1
__
2.
The new positions are found by applying the rules to the step 1 positions.
player 3:
(x, y) ⇒ (x -4, y -2)
3'(-1.5, 0) ⇒ 3''(-1.5 -4, 0 -2) = 3''(-5.5, -2) . . . position after step 2
player 4:
(x, y) ⇒ (x +3, y -2)
4'(1, 0.5) ⇒ 4''(1 +3, 0.5 -2) = 4''(4, -1.5) . . . position after step 2
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.